The Service Marketing Mix and Perceived Service Quality Affecting Communicate Word of Mouth of Accommodation for Rent In Muang District Phitsanulok Province - Khunmathuros, Sitthawut; Seesupan, Tummatinna; Narakorn, Prasittichai (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2021)
The purposes of research were 1) to study the service marketing mix perceived service quality and communicating word of mouth of accommodation for rent in Muang district Phitsanulok province 2) to study the service marketing mix affecting communicate word of mouth of accommodation for rent in Muang district Phitsanulok province 3) to study perceived service quality affecting communicate word of mouth of accommodation for rent in Muang district Phitsanulok province. The research used a quota sampling from 400 simples. The data were collected by questionnaire. Statistics analyzed were percentage, frequency, mean, standard deviation and multiple regression analysis. The research found that 1) the service marketing mix perceived service quality and communicating word of mouth of accommodation for rent in Muang district Phitsanulok province were at a high level 2) the service marketing mix were price, promotion and physical which affected to communicate word of mouth of accommodation for rent in Muang district Phitsanulok province at the statistical significance level of 0.05 which overall had predicted together of 61.2% (R2=0.612) 3) perceived service quality affecting communicate word of mouth of accommodation for rent in Muang district Phitsanulok province were reliability, responsiveness, assurance and empathy which affected to communicate word of mouth of accommodation for rent in Muang district Phitsanulok province at the statistical significance level of 0.05 which overall had predicted together of 60.8% (R2=0.608)